Repurposed and investigational disease-modifying drugs in osteoarthritis (DMOADs). (May 2022) - Oo, Win Min; Hunter, David J.
In spite of a major public health burden with increasing prevalence, current osteoarthritis (OA) management is largely palliative with an unmet need for effective treatment. Both industry and academic researchers have invested a vast amount of time and financial expense to discover the first diseasing-modifying osteoarthritis drugs (DMOADs), with no regulatory success so far. In this narrative review, we discuss repurposed drugs as well as investigational agents which have progressed into phase II and III clinical trials based on three principal endotypes: bone-driven, synovitis-driven and cartilage-driven. Then, we will briefly describe the recent failures and lessons learned, promising findings from predefined post hoc analyses and insights gained, novel methodologies to enhance future success and steps underway to overcome regulatory hurdles.